Identification of trapped electron modes in frequency fluctuation spectra. (26th November 2015) - Arnichand, H; Citrin, J; Hacquin, S; Sabot, R; Krämer-Flecken, A; Garbet, X; Bourdelle, C; Bottereau, C; Clairet, F; Giacalone, J C; Guimarães-Filho, Z O; Guirlet, R; et al.
Abstract: Ion temperature gradient (ITG) and trapped electron modes (TEM) are two important micro-instabilities in the plasma core region of fusion devices ( ). They usually coexist in the same range of spatial scale (around ), which makes their discrimination difficult. To investigate them, one can perform gyrokinetic simulations, transport analysis and phase velocity estimations. In Tore Supra, the identification of trapped electron modes (TEM) is made possible due to measured frequency fluctuation spectra. Indeed, turbulent spectra generally expected to be broad-band, can become narrow in case of TEM turbulence, inducing 'quasi-coherent' (QC) modes named QC-TEM. Therefore the analysis of frequency fluctuation spectra becomes a possible tool to differentiate TEM from ITG. We have found indications that the TEM can have a QC signature by comparing frequency fluctuation spectra from reflectometry measurements, gyrokinetic simulations and synthetic diagnostic results. Then the scope of the analysis of QC-TEM are discussed and an application is shown, namely transitions between TEM turbulence and MHD fluctuations.